The Relationship between Removable Dental Prostheses and Brain Activity in Elderly Individuals: Systematic Review - Arpit Sikri; Jyotsana Sikri; Rinshul Saroch; Charanjeet Singh Gill; Rimple Gupta; Chetan Pathak (Rambam Maimonides Medical Journal)
Background: There is an increasing body of literature associating edentulism with cognitive impairment. The aim of this systematic review was to summarize the available data, emphasizing the role of removable dental prostheses in preventing cognitive deterioration and promoting brain health in elderly individuals.